PENGARUH FREKUENSI PENCELUPAN DAN JENIS MORDAN DARI EKSTRAK DAUN KETAPANG SEBAGAI PEWARNA ALAMI KAIN BATIK - Irsya Qisti Awwalie; Tri Widayatno; Agus Haerudin (Narada : Jurnal Desain dan Seni, 2022)
Ketapang leaves contain tannin pigments of 11% -23% so that they can produce colors ranging from brownish yellow to dark brown. The purpose of this study was to determine how to process ketapang leaves into natural dyes for batik cloth and to determine the effect of dyeing frequency and type of mordant on color sharpness and color fastness. This study uses an experimental method, which is a method that is useful for finding the effect of certain treatments on the conditions to be controlled. The process starts from the selection of the extraction method, namely the reflux method, and the selection of the mordanting process, namely the provision of mordant at the end. The results showed that the effect of dyeing frequency and type of mordant on color sharpness using the L*, a*, b* color test was quite significant. The more the dyeing frequency, the darker the resulting color. The lowest L* value was 53.02 for lime mordant and 20.78 for tunjung mordant with 18 times of immersion frequency. The highest a* value was in lime mordant 12.15 with 18 times of immersion and 8.43 of tunjung mordant with 6 times of immersion. The highest b* value was 38.99 for lime mordant and 11.35 for tunjung mordant with 6 times of immersion frequency. The effect of the frequency of immersion and the type of mordant on the TLW test, namely washing soap and hot ironing dry did not have much significant effect. A good and optimal TLW value found in lime mordant and tunjung is 4 in the good category with 12 times the immersion frequency.